Reduced Activity of the Aortic Gamma-Glutamyltransferase Does Not Decrease S-Nitrosoglutathione Induced Vasorelaxation of Rat Aortic Rings - Perrin-Sarrado, Caroline; Pongas, Marios; Dahboul, Fatima; Leroy, Pierre; Pompella, Alfonso; Lartaud, Isabelle (Frontiers in Physiology, 2016)
Aims: Gamma-glutamyltransferase (GGT), an enzyme present on the endothelium, is involved in the release of nitric oxide (NO) from S-nitrosoglutathione (GSNO) and in the GSNO-induced vasodilation. Endogenous GSNO is a physiological storage form of NO in tissues while exogenous GSNO is an interesting candidate for compensating for the decreased NO bioavailability occurring during cardiovascular diseases. We investigated in a rat model of human hypertension, the spontaneous hypertensive rat (SHR), submitted or not to high salt diet, whether a decreased vascular GGT activity modifies the vasorelaxant effect of GSNO. Methods: Thoracic aortic rings isolated from male SHR and Wistar Kyoto rats (WKY) aged 20-22 weeks - submitted or not for 8 weeks to a high salt diet (1% w/v NaCl in drinking water) were pre-constricted with phenylephrine then submitted to concentration-vasorelaxant response curves (maximal response: Emax; pD2) to carbachol or sodium nitroprusside to evaluate endothelial dependent or independent NO-induced vasodilation, or GSNO (exogenous NO vasodilation depending from the endothelial GGT activity). GGT activity was measured using a chromogenic substrate in aortic homogenates. Its role in GSNO-induced relaxation was assessed following inhibition of the enzyme activity (serine-borate complex). That of protein disulfide isomerase (PDI), another redox sensitive enzyme involved in GSNO metabolism, was assessed following inhibition with bacitracin. Results : Aortic GGT activity (18-23 nmol/min/g of tissue in adult WKY) decreased by 33 % in SHR and 45 % in SHR with high salt diet. Emax and pD2 for sodium nitroprusside were similar in all groups. Emax for carbachol decreased by -14%, reflecting slight endothelial NO-dependent dysfunction. The GSNO curve was slightly shifted to the left in SHR and in SHR with high salt diet, showing a small enhanced sensitivity to GSNO. Involvements of GGT, as that of PDI, in the GSNO effects were similar in all groups (pD2 for GSNO -0.5 to -1.5 following enzymatic inhibition). Conclusion: Hypertension is associated with a decreased aortic GGT activity without decreasing the vasorelaxant effects of GSNO, whose bioactivity may be supplemented through the alternative enzymatic activity of PDI.